In vivo regulation of histidine ammonia-lyase activity from Streptomyces griseus. - Kroening, T A (1987)
The enzyme histidine ammonia-lyase (histidase) is required for growth of Streptomyces griseus on L-histidine as the sole source of nitrogen. Histidase was induced by the inclusion of histidine in the medium, regardless of the presence of other carbon and nitrogen sources. Histidase activity was increased by a shift of culture incubation temperature from 30 to 37 degrees C. Conversely, upon induction of sporulation by either phosphate starvation or nutritional downshift, histidase underwent rapid inactivation. Nutrient replenishment fully reversed histidase inactivation while simultaneously permitting reinitiation of vegetative growth. In contrast to histidase inactivation during sporulation, histidase was activated after transition of a vegetatively growing culture to stationary phase. Although neither activation nor inactivation required de novo protein synthesis, inactivation appeared to involve a heat-labile protein. The results indicate that histidase activity is regulated in vivo by a process that responds to changes in the growth phase of the organism.